Development of the Common Cognitive Complaints after Concussion (C4) questionnaire: a treatment-planning tool for military service members and veterans with mild traumatic brain injury - Mollie Ann McDonald; Lisa H. Lu; Lisa H. Lu; Lisa H. Lu; Glenn Curtiss; Douglas B. Cooper; Douglas B. Cooper; Amy O. Bowles; Melissa R. Ray; M. Marina LeBlanc; Blessen C. Eapen; Blessen C. Eapen; et al. (Frontiers in Neurology, 2025)
ObjectiveTo develop an activity-focused self-report tool to guide selection of treatment targets in cognitive rehabilitation for adults with mild traumatic brain injury (mTBI).SettingMilitary and veteran treatment facilities.ParticipantsTwenty-one service members and 32 veterans with a history of mTBI; 25 veterans with orthopedic injury (OI).DesignClinical tool development.Main measuresCommon Cognitive Complaints after Concussion (C4) questionnaire.ResultsWe reviewed measures used in mTBI research or clinic, to identify items that could be used for selecting activity-level therapy targets as part of a treatment planning tool. To establish face and content validity, an initial item pool was reviewed by five speech-language pathology or occupational therapy mTBI experts who selected items relevant to their clinical practice, gave feedback on item wording, and suggested additional items. The result was a questionnaire with 22 activity-based items and one bias-check item. The C4 was then used in a feasibility mTBI treatment trial to identify treatment targets, and clinicians provided feedback on its utility. The C4 was also administered to an OI group to evaluate the distinctiveness of the items to mTBI symptoms.ConclusionThe C4 adequately captured activity-level functional impairments common to mTBI, and clinicians endorsed its utility as a useful tool to personalize treatment targets.